(untitled) (Philological Studies, 2024)
Translating idioms can be a great challenge when they are transferred from the source language into the target language. When using idioms, knowledge of language can be perceived, and when translating them, comprehension and the ability to express yourself in another language can be recognized. Through the use of idioms, one can see the way of thinking and the point of view of a nation. The aim of this paper is to give an outline of the level of equivalence between English and Macedonian idiomatic expressions. Hence, the paper examines the idiomatic expressions in English and their translation equivalents in Macedonian. The analysis has been conducted on a corpus of sentences excerpted from two novels written in English by the Turkish-British writer Elif Shafak and their translation equivalents in Macedonian. The analysis of the excerpted corpus of sentences has been classified into three groups. Regarding the English idiomatic expressions, there are full (direct) equivalents,partial (approximate) equivalents, as well as no equivalents in Macedonian.